The Utilization of VO₂Max Data as Archery Athlete Selection and Monitoring Instrument - I Gede Ari Septena Putra; Kadek Yogi Parta Lesmana; I Made Satyawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
In sports management in schools, objectivity in the athlete selection process is often compromised due to the lack of use of measurable and scientific-based physical data. In archery, aerobic capacity, especially VO₂max, plays an important role in maintaining physical stability, concentration, and heart rate stability during matches. This study aims to implement VO₂max audit as a strategic instrument in the selection, evaluation, and monitoring of archery athletes at SMK Negeri Bali Mandara. A descriptive quantitative approach was used with 21 archery athletes. VO₂max was measured using the Multistage Fitness Test (MFT). The results showed that athletes' aerobic capacity ranged from 22.93 to 38.84 ml/kg/min, with the majority (52.4%) in the "Adequate" category. These findings indicate that most athletes still need to improve their physical condition. The data from this fitness audit can be used as a basis for grouping more effective and directed training programs. In addition, the VO₂max audit provides a scientific foundation for more transparent, objective, and accountable managerial decision-making in the school sports environment.